About the Features of Perception of Social Entrepreneurship in the World - Akhmetshin, Renat Maksutovich; Gayazova, Elvira Bayazitovna (Journal of History Culture and Art Research, 2017)
The progressive business community understands that social responsibility will eventually become mandatory. The social responsibility concept changes essentially the image about the role of entrepreneurship in the modern society. It generates the modern request of all world society - the social entrepreneurship phenomenon. The purpose of this paper is to analyze the best practices of implementing social entrepreneurship in the current macroeconomic conditions in Russia and in the world. As a theoretical background of the research, systemic, structural and functional approaches were applied to the analysis of social entrepreneurship in Russia and in the world as elements of the economic system, related to other elements of the social system - civil society and government.